2004
DOI: 10.1097/01.nmd.0000146737.18053.d2
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Psychiatric Inpatients’ Self-Reported Reasons for Cutting Themselves

Abstract: To ascertain (1) whether male and female adolescent (13-17 years old) psychiatric inpatients endorse comparable reasons for cutting themselves and (2) whether these reasons are correlated with selected psychosocial characteristics of the adolescents, self-reported depression, and hopelessness, the Self-Injury Motivation Scale II (SIMS-II), the Beck Depression Inventory-II, and the Beck Hopelessness Scale were administered to 19 (38%) male and 31 (62%) female adolescents who had cut themselves. Independent t te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 16 publications
5
69
0
6
Order By: Relevance
“…3 1 The self-cutting behavior, though confusing to others, often serves as a way of releasing intense and unbearable pain from suppressed negative feelings driven by underlying depression and anxiety from conflicts with family and/or peers. 12,19,[66][67][68] On the other hand, social support was found to be an important protective factor against suicidal ideation.…”
Section: Etiology Of Deliberate Self-harmmentioning
confidence: 99%
“…3 1 The self-cutting behavior, though confusing to others, often serves as a way of releasing intense and unbearable pain from suppressed negative feelings driven by underlying depression and anxiety from conflicts with family and/or peers. 12,19,[66][67][68] On the other hand, social support was found to be an important protective factor against suicidal ideation.…”
Section: Etiology Of Deliberate Self-harmmentioning
confidence: 99%
“…The most common mood disorder associated with suicide is depression, with 87% of those who died by suicide presenting with symptoms of depression [8]. Another serious risk factor is bipolar disorder.…”
Section: The Scope Of the Phenomenon Of Suicidementioning
confidence: 99%
“…In adults, the wish to put an end to intolerable tension in the context of overwhelming affect emerges as a commonly reported reason for cutting (Suyemoto 1998;Yip 2002). Several studies have noted that young people report a 'sense of relief' when they cut themselves (Kumar 2004;Laye-Gindhu 2005). This affect regulation perspective involves reducing undesired emotional states (Nock 2010) or controlling emotions such as anger, anxiety, guilt or sadness in the face of stress and mounting tension (Machoian 2001;).…”
Section: Emotion Regulation and Copingmentioning
confidence: 99%
“…Adolescents psychiatric in-patients who had cut themselves reported that self-injury helped them 'cope with feelings of depression', and depressive symptomatology was associated with the number and intensity of motivations for cutting behaviours (Kumar 2004). Menninger (1938) described self-harm as an effort to avert completed suicide, with a 'sense of relief' that suicide has been avoided (Pattison 1983).…”
Section: Depressive Illnessmentioning
confidence: 99%